2000
DOI: 10.1182/blood.v95.8.2600.008k28_2600_2609
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the human platelet F11 receptor: a cell adhesion molecule member of the immunoglobulin superfamily involved in platelet aggregation

Abstract: This study demonstrates that the human platelet F11 receptor (F11R) functions as an adhesion molecule, and this finding is confirmed by the structure of the protein as revealed by molecular cloning. The F11R is a 32-/35-kd protein duplex that serves as the binding site through which a stimulatory monoclonal antibody causes platelet aggregation and granule secretion. A physiological role for the F11R protein was demonstrated by its phosphorylation after the stimulation of platelets by thrombin and collagen. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 56 publications
1
59
0
Order By: Relevance
“…One example consists of the domain comprising the epitope for F11, an antibody for which JAM-A/F11R was originally named. 37 Peptides mimicking part of the distal Ig domain (D1) block both F11 binding to JAM-A and platelet adhesion to endothelial cells. 11 However, these peptides map to a different area on D1 that is distinct from the cisdimerization region, 17 indicating a potentially separate functional domain.…”
Section: Other Potential Interacting Domains On Jam-amentioning
confidence: 99%
“…One example consists of the domain comprising the epitope for F11, an antibody for which JAM-A/F11R was originally named. 37 Peptides mimicking part of the distal Ig domain (D1) block both F11 binding to JAM-A and platelet adhesion to endothelial cells. 11 However, these peptides map to a different area on D1 that is distinct from the cisdimerization region, 17 indicating a potentially separate functional domain.…”
Section: Other Potential Interacting Domains On Jam-amentioning
confidence: 99%
“…The extracellular segment comprises two Ig-like domains, an amino terminal (VH-type) and a carboxyl terminal (C2-type) ␤-sandwich fold. The same VH-C2 tandem arrangement occurs in human, rat, and cow JAM-1 (68% to 75% sequence identity) (41,55,68,78), as well as in JAM-2 (7) and JAM-3 (18,57), two recently identified molecules with more than 30% identity with JAM-1. These data point to the existence of a family of JAM proteins that share a common VH-C2 structure, as well as the ability to localize at intercellular junctions and possibly to regulate permeability.…”
Section: The Extracellular Domain Of Jam-1: Molecular Determinants Ofmentioning
confidence: 69%
“…Description of these molecular associations opens several questions. For instance, as thrombin and collagen induce phosphorylation of JAM-1 in platelets (68), possibly due to protein kinase C activation (56), does JAM-1 phosphorylation modulate the associations of JAM-1 with its known intracellular partners? Also, as ZO-1, CASK, and AF-6 all bind JAM-1 in a PDZ-dependent manner, is the binding to JAM-1 mutually exclusive or, alternatively, do distinct complexes coexist at mature junctions?…”
Section: The Intracellular Domain Of Jam-1: Molecular Determinants Ofmentioning
confidence: 99%
“…Studies in which oncolytic reovirus was delivered intravenously to persons with cancer revealed that virus is largely found in hematopoietic cells, specifically mononuclear cells, granulocytes, and platelets (Adair et al, 2012). Each of these cell types express JAM-A (Martin-Padura et al, 1998;Naik et al, 2001;Sobocka et al, 2000), suggesting that reovirus associates with or infects blood cells to disseminate through the blood to target organs. However, in these studies, virus was delivered directly into the bloodstream by intravenous inoculation.…”
Section: B Reovirus Viremiamentioning
confidence: 99%